IMPROVEMENT OF JAPANESE MILITARY CAPABILITIES AND IMPLICATIONS ON INDONESIA’S NATIONAL DEFENSE - Marsono Marsono; Deni D.A.R.; Novky Asmoro (The Republic of Indonesia Defense University, 2018)
Abstract - In the historical record, Japan was among the most prominent country in military aspect. Japanese military force at that time was evidenced by the strength of their personnel and equipment. This article aims to explore and analyze the development of Japanese military capabilities and ascertaining its implication on ASEAN and the defense of Indonesia. This study uses data analysis technique and narrative qualitative methods, each data that has been collected and validated will be analyzed through data reduction, data presentation, and conclusion/verification. From this study, it can be concluded that the improvement of Japanese military capabilities is strongly related to the interest and conflict between several countries such as China, Japan and North Korea. Therefore, Indonesia needs to have preventive measure in anticipating the rise or improvement of Japanese military capabilities even if it has a harmonious cooperation with Japan in many aspects. After all, Indonesia was one of the direct victims of Japanese imperialism and militarism.